Depression and Anxiety in adolescents practicing sports and Physical Education classes (Research, Society and Development, 2022)
The objective of this research was to evaluate and compare the levels of depression and anxiety in adolescents who practice sports and adolescents who practice physical education classes. This is a quantitative, descriptive, longitudinal study, composed of adolescents aged 16.25 +_0.99 years old from the city of Anápolis-Go, with 211 participants. To assess symptoms of depression, the BDI test was used and for the anxiety symptom, the IAB was used, a linear Pearson correlation, a “t” test for independent samples and analysis of variance (One-Way ANOVA.) The results found are that the level of anxiety in sports practitioners (26.52±10.52) is higher than in students who only practice physical education classes (13.57±10.00) And there was a correlation of that the greater the weight and height, the higher the scores for anxiety (r-.266** and -.369**) and for depression (-.235** and -.330**). Females still have higher anxiety and depression scores regardless of whether they are athletes or not. Sport helps control depression, but in the pre-competitive phase it can increase state anxiety levels.